Mitogenomics data reveal effective population size, historical bottlenecks, and the effects of hunting on New Zealand fur seals (Arctocephalus forsteri). (19th May 2018) - Emami-Khoyi, Arsalan; Paterson, Adrian M.; Hartley, David A.; Boren, Laura J.; Cruickshank, Robert H.; Ross, James G.; Murphy, Elaine C.; Else, Terry-Ann
Abstract: The New Zealand fur seal ( Arctocephalus forsteri ) passed through a population bottleneck due to commercial sealing during the eighteenth to nineteenth centuries. To facilitate future management options, we reconstructed the demographic history of New Zealand fur seals in a Bayesian framework using maternally inherited, mitochondrial DNA sequences. Mitogenomic data suggested two separate clades (most recent common ancestor 5000 years ago) of New Zealand fur seals that survived large-scale human harvest. Mitochondrial haplotype diversity was high, with 45 singletons identified from 46 individuals although mean nucleotide diversity was low (0.012 ± 0.0061). Variation was not constrained geographically. Analyses of mitogenomes support the hypothesis for a population bottleneck approximately 35 generations ago, which coincides with the peak of commercial sealing. Mitogenomic data are consistent with a pre-human effective population size of approximately 30, 000 that first declined to around 10, 000 (due to the impact of Polynesian colonization, particularly in the first 100 years of their arrival into New Zealand), and then to 100–200 breeding individuals during peak of commercial sealing.